The Association Between the Pattern of Electronic Cigarette Smoking and Gastroesophageal Reflux - Ahmad Fariz Malvi Zamzam Zein; Donny Nauphar; Uswatun Khasanah; Tiar M Pratamawati; Rama S Brajawikalpa; Eka Ayuningtyas; Alif Hamzah (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2021)
Background: This study was aimed to investigate the proportion of gastroesophageal reflux (GER) among electronic cigarette (e-cig) smokers and its association with the pattern of e-cig smoking.Method: This cross-sectional study underwent among e-cig smokers community in Cirebon City, Jawa Barat, ranged from March to August 2020. Subjects were enrolled through consecutive sampling method. The data collection used survey containing the pattern of e-cig smoking and GER. The pattern of e-cig smoking included the duration of e-cig smoking and the amount of e-cig smoking. Gastroesophageal reflux consisted of GER-related symptoms (heartburn, regurgitation, and nocturnal symptom) and gastroesophageal reflux disease (GERD). GERD was defined as GERD questionnaire score cut-off 8. Data analysis used chi square test. This study has been approved by The Medical Research Ethics Committee, Faculty of Medicine, Universitas Swadaya Gunung Jati.Results: There were 273 respondents in this study. The proportion of heartburn was 6.6%, 10.3% for regurgitation, 3.7% for nocturnal symptom, and 5.5% for GERD. There was no association between duration of e-cig smoking and heartburn (p 0.681), regurgitation (p 0.568), nocturnal symptom (p 0.764), and GERD (p 0.113). There was no association between amount of e-cig smoking and heartburn (p 0.062), regurgitation (p 0.770), nocturnal symptom (p 0.985), and GERD (p 0.605).Conclusion: There was relatively low proportion of GER among e-cig smokers. There was no association between the pattern of e-cig smoking and GER in this study.